Chondroprotection and the Prevention of Osteoarthritis Progression of the Knee: A Systematic Review of Treatment Agents. (March 2015) - Gallagher, Brian; Tjoumakaris, Fotios P.; Harwood, Marc I.; Good, Robert P.; Ciccotti, Michael G.; Freedman, Kevin B.
Background: Structure-modifying medications or nutraceuticals may be an effective treatment for osteoarthritis. This study identified 12 treatments that may possess chondroprotective properties: oral glucosamine; chondroitin; nonsteroidal anti-inflammatory drugs (NSAIDs); polyunsaturated fatty acids; S-adenosylmethionine; avocado and soybean unsaponifiable fractions; methylsulfonylmethane; vitamins C, D, and E; intra-articular injections of hyaluronic acid; and platelet-rich plasma (PRP). Purpose: To perform a systematic review of randomized controlled trials for the effectiveness of each agent in preserving articular cartilage of the knee and delaying the progression of osteoarthritis. Study Design: Systematic review; Level of evidence, 2. Methods: A literature search was performed using PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials. Searches were performed using "treatment, " "osteoarthritis, " and "knee" as keywords. Selection criteria included randomized controlled trials of ≥12 months, with a placebo control, measuring radiographic changes in joint space width, cartilage volume, or radiographic progression of osteoarthritis. The primary outcome was changes in joint integrity measures. Results: A total of 3514 studies were identified from the initial search, 13 of which met inclusion criteria. Treatment with chondroitin sulfate showed a significant reduction in cartilage loss in 3 of 4 studies identified compared with placebo. Two of 3 trials identified for glucosamine also reported significant structural effects relative to placebo. Intra-articular hyaluronic acid was effective in lowering the rate of cartilage loss in only 1 of 3 studies identified versus placebo. Of the 6 studies identified for NSAIDs, vitamin E, and vitamin D, none showed any structural effect compared with placebo. No studies were found that met the inclusion criteria for polyunsaturated fatty acids, S-adenosylmethionine, avocado and soybean unsaponifiable fractions, methylsulfonylmethane, vitamin C, or PRP. Conclusion: For patients with or at risk for osteoarthritis, the use of glucosamine and chondroitin sulfate may serve as a nonoperative means to protect joint cartilage and delay osteoarthritis progression. Hyaluronic acid injections showed variable efficacy, while NSAIDs and vitamins E and D showed no effect on osteoarthritis progression. The other agents evaluated had no evidence in the literature to support or refute their use for chondroprotection.